Comparing behavioural and rational expectations for the US post-war economy - Chunping Liu; Patrick Minford (Cardiff University, Cardiff Business School, 2012)
The banking crisis has caused a resurgence of interest in behavioural models of expectations in macroeconomics. Here we evaluate behavioural and rational expectations econometrically in a New Keynesian framework, using US post-war data and the method of indirect inference. We find that after full re-estimation the model with behavioural expectations is strongly rejected by the data, whereas the standard rational expectations version passes the tests by a substantial margin.
Keywords: 330; behavioural expectation; rational expectation; bank crisis; indirect inference